Evaluation of the Science Learning Process at SMPN 5 Bengkulu Based Online During the Pandemic - Engga Marlinsa; Freti Saputri; mardiyati mardiyati; Ahmad Walid (Asian Journal of Science Education, 2021)
The purpose of this study was to evaluate the student learning process in science subjects at SMPN 5 Bengkulu online based during the pandemic. The method used is a data analysis method with a descriptive qualitative approach to the sources obtained through interviews and filling in the Google Form wich is distributed to students of class VII and IX of SMPN 5 Bengkulu. The instrument used in this study was a questionnaire. The results showed that online learning was quite fun for students with a percentage of 67.6% and boring for other 32.4% students. And the Whatsapp application is more effectively used in online learning with a percentage of 91.2%, besides that handphone can also be useful for students in the learning process because they are easy to use.